Barnfri: en stigmatiserad position (Sociologisk Forskning, 2011)
Childfree: a stigmatized positionInternational research has addressed the subject but in Sweden voluntary childlessness has until now been overlooked. This article draws on qualitative, semi-structured interviews with 21 Swedish childfree women. The interviews focused their decision not to have children and attitudes they faced due to their rejection of motherhood. They all had encountered pressure to conform to a pronatalistic norm, proclaiming parenthood to be self-evident in an adult normal life. The results highlight different strategies used by the women to avoid instigating the dislike of those around them. The article argues that understanding childfree as a stigmatized position helps providing new insights to what conditions the social relations between the childfree and ‘the normals’, i.e. persons who advocate having children. Further, viewing the childfree as a stigmatized group has theoretical implications that contribute to developing Goffman’s classical theory of social stigma.
Keywords: childfree women; pronatalistic norms; stigmatization; stigma management